Design of a 3D space early warning system for high precision positioning technology of Beidou and analysis of differential positioning accuracy - Xingzhi Chang; Weizheng Pei; Limin Zhang; Yanfei Zhang; Qingshan Yuan (Measurement: Sensors, 2024)
The Beidou satellite navigation system has achieved certain results in positioning accuracy, but due to factors such as system errors, its accuracy still does not fully meet the requirements of high-precision measurement. Therefore, this study proposes a design method for a three-dimensional space early warning system, aiming to combine the positioning function of the BeiDou satellite navigation system and differential positioning technology to improve positioning accuracy. By utilizing differential positioning technology, multiple reference stations are arranged around the receiving device, and the positioning information received by these stations is used for accuracy correction. This method can effectively offset errors such as atmospheric errors, clock errors, and multipath effects between receivers, making the obtained positioning results more accurate. Through the design and implementation of a three-dimensional space early warning system, positioning errors can be predicted and monitored, and abnormal positioning situations can be detected and corrected in a timely manner, thereby improving the overall reliability of positioning. The system designed in this article can effectively improve positioning accuracy, meet the requirements of modern measurement technology for positioning accuracy, and demonstrate the superiority of the system through experimental verification and differential positioning accuracy analysis.